2008
DOI: 10.1038/sj.mp.4002148
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced depressive-like behavior is mediated by indoleamine 2,3-dioxygenase activation in mice

Abstract: Although elevated activity of the tryptophan-degrading enzyme indoleamine 2,3-dioxygenase (IDO) has been proposed to mediate comorbid depression in inflammatory disorders, its causative role has never been tested. We report that peripheral administration of lipopolysaccharide (LPS) activates IDO and culminates in a distinct depressive-like behavioral syndrome, measured by increased duration of immobility in both the forced-swim and tail suspension tests. Blockade of IDO activation either indirectly with the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

71
1,021
5
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,123 publications
(1,107 citation statements)
references
References 53 publications
71
1,021
5
10
Order By: Relevance
“…In support of this hypothesis, Raison et al (2010) reported that INFa-treated hepatitis C patients showed both plasma and CSF increases in KYN and QA that correlated with depressive symptoms. Furthermore, peripheral administration of KYN has been shown to induce behavioral analogs of depression in rodents (O'Connor et al, 2009), andLaugeray et al (2011) reported that mice subjected to chronic mild stress showed a peripheral increase in kynurenine pathway activity that was inversely correlated with KA concentration in the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, Raison et al (2010) reported that INFa-treated hepatitis C patients showed both plasma and CSF increases in KYN and QA that correlated with depressive symptoms. Furthermore, peripheral administration of KYN has been shown to induce behavioral analogs of depression in rodents (O'Connor et al, 2009), andLaugeray et al (2011) reported that mice subjected to chronic mild stress showed a peripheral increase in kynurenine pathway activity that was inversely correlated with KA concentration in the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment of mice with the competitive IDO inhibitor 1-methyltryptophan (1-MT) decreased the effectseverity of repeated acoustic + restraint stress on physical condition and motor inactivity (Kiank et al, 2010). Pre-treatment with 1-MT prevented systemic LPS, which activates the IDO1-KYN pathway, from decreasing mouse activity in FST and TST (O'Connor et al, 2009b).…”
Section: Integrating Current Findings With Existing Evidence For Kyn-mentioning
confidence: 99%
“…Antidepressant-like effects of minocycline have been demonstrated in several animal models (Henry et al, 2008, O'Connor et al, 2009, Hinwood et al, 2012, Arakawa et al, 2012, with recent data expanding this to include the OB rat. Specifically, chronic minocycline has been demonstrated to attenuate OB-related hyperactivity, behavioural despair (forced swim test) and spatial memory deficits (Borre et al, 2012, Rinwa andKumar, 2013).…”
Section: Antidepressant-like Effects Of Chronic Minocycline In the Obmentioning
confidence: 99%
“…Antidepressant efficacy of minocycline, a second-generation antibiotic that also inhibits microglial activation, has been reported both clinically (Miyaoka et al, 2012) and in animal models (Henry et al, 2008, O'Connor et al, 2009, Arakawa et al, 2012, Hinwood et al, 2012. Furthermore, minocycline has been shown to be beneficial in pain states such as rheumatoid arthritis (Langevitz et al, 2000) and sciatica (Sumracki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%